ANTISIPASI POTENSI KONFLIK SOSIAL ANTAR PELAJAR - Ghofar, Abdul (AL-MISBAH (Jurnal Islamic Studies), 2014)
Conflict is motivated by differences in the characteristics of individuals brought in an interaction. These differences are related to the physical characteristics including, intelligence, knowledge, customs, beliefs, and so forth. With individual characteristics in social interaction, conflict is a normal situation in each community. None of the people who have never experienced any conflicts between members or with other community groups, the conflict will only disappear with the loss of the community itself. Results of a conflict are: 1) Increase the solidarity among members of the group (in-group) which is in conflict with the group elsewhere.2) Rift between the warring factions. 3) Personality changes in individuals, 4) Property damage and loss of human lives. 5) The dominance of conquest even one of the parties involved in the conflict.    Attempts to defuse conflicts in achieving stability is called ?accommodation?.The parties in conflict with each other adjust to the situation by working together. Forms of accommodation are: 1) truce, 2) Abitration, 3) Mediation, 4) Conciliation, 5). Stalemate, and 6) Adjudication. Young people or students have great potential in solving the nation?s problems, particularly issues related to the anticipation of social conflict, although there is no doubt that the problem of the young generation too much. The important thing is to be able to change his awareness of the construction of the object becomes the subject of development and able to anticipate these issues.